Coping Strategies Adopted by Motor Vehicle Accident Survivors from a Hilly State of North India. Issue 1 (January 2023) - Arora, Deeksha; Belsiyal, Xavier C.; Rawat, Vikram Singh
Background: Dealing with trauma has always been challenging for people from all walks of life. Moreover, traumas like Motor Vehicle Accidents (MVA) are sudden and can be life-threatening, which further raises the concern and thus requires healthy adaptation. Considering the lack of data on the coping strategies of accident survivors in India, this study was undertaken to assess the coping strategies adopted by MVA survivors. Methods: Cross-sectional survey was conducted at tertiary care institution in Uttarakhand (India) during 2019–2020. A total of 250 MVA survivors were selected through total enumerative sampling and assessed for posttraumatic stress disorder (Posttraumatic Stress Disorder Checklist (PCL)-5), depression (Zung self-rating depression scale), and coping strategies (Brief COPE questionnaire). Results: The mean score was highest for emotion-focused coping mechanism (32.84± 5.18) and lower for dysfunctional (26.18± 10.59) and problem-focused (18.47± 3.12) coping mechanisms. Religion (96.87%) and emotional support (87.25%) were among the frequently adopted coping styles, whereas denial and self-blame were the least adopted. A high correlation was found between depression and the three coping mechanisms ( r = 0.83 [emotion-focused coping], 0.68 [problem-focused coping], 0.62 [dysfunctional coping]). Among the participants, 133 crossed the threshold for PTSD and/or depression. Conclusions: A commonly adopted coping strategy among MVA survivors is emotion-focused coping mechanism. Religion and emotional support are most prevalent because of family dynamics prevalent in countries like India.